The Enduring Ecological Consequences of the COVID-19 Epidemic and Corresponding Government Actions - Goren, Sami (European Journal of Applied Sciences, 2024)
Following the start of the COVID-19 pandemic in December 2019, there was a notable global decrease in the quantity of human activities. Due to the catastrophic consequences this epidemic had on people’s health and quality of life, there was a sharp decline in activity levels. Travel restrictions, social isolation, and lockdowns are a few of the precautionary measures that governments and health organisations have recommended to stop the virus from spreading further. Significant environmental improvements, such as a decrease in air pollution and other environmental issues, have been brought about by the decline in human activity. The effects of climate change are what have caused these modifications. This study aims to look into the data on the reduction in environmental pollutants that occurred as a result of COVID’s implementation. The study calls for the use of a cautious approach to locate data from reliable sources, such as government and non-governmental organisations, academic research papers, and other sources, in order to find patterns in the levels of pollution in the air, water, and soil as well as in waste management, biodiversity, and greenhouse gas emissions. This is done in an effort to identify global trends in pollution levels. According to the study’s findings, pollution levels have significantly decreased globally, indicating that favourable changes in the environment may yet transpire. This outcome is the consequence of verifying the available data. Furthermore, it addresses the implications for policy initiatives as well as possible long-term repercussions.